Evaluación de la composición nutricional, antinutricional y biodisponibilidad in vitro de diferentes extractos foliares - Pico, S; Gutiérrez, D.; Aragón Gallego, Ingrid J.; Escobar, A.; Ortíz, D.; Sánchez, T.; Imbachí Narváez, P.C.; Pachón, Helena (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
Foliar extracts (FEs) are an alternative to address food and nutrition insecurity. FEs and leaves of cassava, bean, sweet potato and alfalfa were evaluated for nutrient and antinutrient composition and in vitro nutrient bioavailability. Bean FE had a high average ± (SD) iron concentration (1006 ± 8.49 mg/kg), as did cassava FE for zinc (110.1 ± 6.72 mg/kg) and soluble protein (34.23 ± 3.81 g/kg) concentration. For the cassava, bean and alfalfa FEs in vitro protein digestibility was greater than 71.18%; in vitro iron dialyzability was less than 2.29%; the phytate:zinc molar ratio was less than 0.08, and the in vitro all-trans-β-carotene bioavailability was greater than 23.85%. These values suggest a high protein, zinc and all-trans- β -carotene bioavailability and a low iron bioavailability. FEs can be a nutritious alternative for those countries with low dietary diversity.